2012
DOI: 10.4172/2161-0533.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Modifies Oblique Proximal Tibial Osteotomy for Deformity Correction of Tibia Vara (Blount Disease)

Abstract: Background: In Blount's disease, there is a complex three-dimensional deformity which typically includes varus, internal rotation, and (sometimes) procurvatum. The best way to obtain correction is with simple procedure carried out as high in the tibia as possible to promote rapid union, quick remodeling, and with minimal proximal shaft deformity. Patients and methods: 17 patients with tibia vara underwent corrections of deformity associated with tibia vara by modified Rab proximal tibial oblique osteotomy at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Acute correction with internal fixation has been widely used in correction of proximal tibial deformity in small children and successful correction has been reported. 3 , 4 However, some studies reported inaccurate correction and malunion. Aly 19 reported that only 67% to 75% of cases achieved accurate correction, which was within 5° of normal value (MPTA 87°), by acute correction with Kirschner-wire cross pinning in children of two to four years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute correction with internal fixation has been widely used in correction of proximal tibial deformity in small children and successful correction has been reported. 3 , 4 However, some studies reported inaccurate correction and malunion. Aly 19 reported that only 67% to 75% of cases achieved accurate correction, which was within 5° of normal value (MPTA 87°), by acute correction with Kirschner-wire cross pinning in children of two to four years of age.…”
Section: Discussionmentioning
confidence: 99%
“…There are several surgical options, including asymmetric physeal suppression, 1 gradual correction using an external fixator 2 and acute correction with internal fixation. 3 , 4 Asymmetric physeal suppression by temporary hemiepiphysiodesis or guided growth is a less invasive procedure, with fewer complications. 5 , 6 However, in small children with genetic or metabolic skeletal disorders, it could be technically demanding for hypoplastic or dysplastic epiphysis.…”
Section: Introductionmentioning
confidence: 99%
“…The limited internal fixation with crossed screws provided satisfactory control of the osteotomy position. 12 Elzohairy et al 2 described 17 patients with tibia vara. A total of 29 tibiae underwent corrections of the deformity associated with tibia vara by modified Rab proximal tibial oblique osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…According to Schoenecker's criteria, 100% of the patients in this study had a good result. 2 Zayer et al 8 published a case report of two neglected cases of Blount's disease with severe sloping of the medial tibial condyle and excessive ligamentous laxity. They did elevation of the medial tibial condyle with good results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation